2010
DOI: 10.1111/j.1600-048x.2009.04902.x
|View full text |Cite
|
Sign up to set email alerts
|

Population structure in the South American tern Sterna hirundinacea in the South Atlantic: two populations with distinct breeding phenologies

Abstract: The South American tern Sterna hirundinacea is a migratory species for which dispersal, site fidelity and migratory routes are largely unknown. Here, we used five microsatellite loci and 799 bp partial mitochondrial DNA sequences (Cytochrome b and ND2) to investigate the genetic structure of South American terns from the South Atlantic Ocean (Brazilian and Patagonian colonies). Brazilian and Patagonian colonies have two distinct breeding phenologies (austral winter and austral summer, respectively) and are und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 53 publications
5
19
0
6
Order By: Relevance
“…Few other possible cases of population differentiation due to allochrony have been reported, and most populations that differ in breeding phenology also differ in other features such as ocean regime (e.g., South American Tern Sterna hirundinacea; Faria et al 2010). Furthermore, many colonies show strong breeding synchrony, and allochrony cannot occur in strongly seasonal ocean regimes.…”
Section: Support From the Literaturementioning
confidence: 95%
“…Few other possible cases of population differentiation due to allochrony have been reported, and most populations that differ in breeding phenology also differ in other features such as ocean regime (e.g., South American Tern Sterna hirundinacea; Faria et al 2010). Furthermore, many colonies show strong breeding synchrony, and allochrony cannot occur in strongly seasonal ocean regimes.…”
Section: Support From the Literaturementioning
confidence: 95%
“…Dispersal results in gene flow between colonies and between geographic regions (Szczys et al, 2005;Draheim et al, 2010;Faria et al, 2010), and may also allow terns to respond quickly to changes in climate or other ecological factors (Møller et al, 2006). Lack of dispersal, on the other hand, contributes to genetic differentiation (Sruoga et al, 2006;Szczys et al, 2012;Boutilier et al, 2014) and can prevent recovery of genetic variation in small populations .…”
Section: Philopatry and Dispersalmentioning
confidence: 99%
“…Because of the flight ability of terns, it is likely that any limits to immigration and emigration are behavioral rather than physical (Matthiopoulos et al, 2005;Faria et al, 2010). Behaviors that affect the frequency of movement among colony sites include site fidelity (philopatry), natal and breeding dispersal, and group adherence.…”
Section: Philopatry and Dispersalmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Boessenkool et al (2009) used multilocus assignments in their study of yelloweyed penguins Megadyptes antipodes and found evidence of rare migration events that would not likely have been detected otherwise. Similarly, Hall et al (2009) used molecular assignments to characterize dispersal patterns in marbled murrelets Brachyramphus marmoratus in central California, and Faria et al (2010) used both molecular assignments and methods based on coalescent theory to infer source− sink dynamics in South American terns Sterna hirundinacea. In an innovative modification of molecular assignments known as parent-offspring dyad analysis, Peery et al (2008) determined that the central California population of marbled murrelets is a demographic sink.…”
Section: Ecologymentioning
confidence: 99%